1992
DOI: 10.1111/j.1399-0004.1992.tb03259.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐inactivation in girls with Rett syndrome

Abstract: Cytogenetic studies have been carried out on a series of nine girls with Rett syndrome, six of their mothers and nine normal female controls. No abnormality of the X‐chromosome has been observed in any subject. X‐inactivation studies using various methods of detecting the timing of individual band replication were performed. The overall pattern seen was essentially the same in all subjects, but in the patients with Rett syndrome there may be an alteration in the timing of the X‐inactivation process in the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Subsequently, Martinho et al (1990) found differences in the X-chromosome inactivation process between chromosomes of normal women and RS patients. Our results are similar to the findings of Kormann-Bortolotto et al (1992). They also observed alteration in the timing of the X-inactivation process in the Xp21 region.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Subsequently, Martinho et al (1990) found differences in the X-chromosome inactivation process between chromosomes of normal women and RS patients. Our results are similar to the findings of Kormann-Bortolotto et al (1992). They also observed alteration in the timing of the X-inactivation process in the Xp21 region.…”
Section: Discussionsupporting
confidence: 92%
“…Riccardi (1986) and Martinho et al (1990) observed different changes in the replicating banding pattern on the late-replicating X chromosome (LRX). Kormann-Bortolotto et al (1992) detected an alteration in replication-timing of the LRX short arm. In addition X-inactivation mosaicism has been suggested (Francke & Schanen 1994).…”
Section: Chromosome Inmentioning
confidence: 99%
“…In all, 23 Rett syndrome probands and their families participated in this study. Of these, 13 had been the subject of previous studies (Kormann-Bortolotto et al 1992, Webb et al 1993) and had been examined by one of the authors. A further five families were ascertained by Dr. Alison Ken and five from other sources.…”
Section: Ascertain Rn En Tmentioning
confidence: 99%
“…The great majority of cases are sporadic, severely limiting linkage studies and suggesting that the syndrome is the result of a de now mutation of an X-linked dominant gene which is lethal in males (Comings 1986). However any disruption in the X-inactivation process could also lead to a female-limited disease and discrepancies in X-heterochromatisation have been described (Riccardi 1986, Martinho et al 1990, Kormann-Bortolotto et al 1992. Occasional reports of non-random X-inactivation in Rett syndrome (Zoghbi et al 1990) precipitated a study of X-inactivation in probands compared to controls in order to investigate whether X-inactivation may be disturbed in Rett syndrome (Webb et al 1993).…”
mentioning
confidence: 99%